2015
DOI: 10.1038/ki.2015.65
|View full text |Cite
|
Sign up to set email alerts
|

Novel in vivo techniques to visualize kidney anatomy and function

Abstract: Intravital imaging using multiphoton microscopy (MPM) has become an increasingly popular and widely used experimental technique in kidney research over the past few years. MPM allows deep optical sectioning of the intact, living kidney tissue with submicron resolution which is unparalleled among intravital imaging approaches. MPM has solved a long-standing critical technical barrier in renal research to study several complex and inaccessible cell types and anatomical structures in vivo in their native environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 69 publications
(150 reference statements)
0
55
0
Order By: Relevance
“…The present study confirmed the presence and passage of albumin-containing vesicles in the Bowman’s space in the rat PAN model. A recent report documented the rupture of albumin-containing pseudocysts that resulted in the emptying of the high albumin-containing cyst fluid into the Bowman’s space and downstream the nephron [25]. Albumin endocytosis by injured podocytes and the rupture of albumin-containing large pseudocysts are likely alternative mechanisms of albumin leakage through the GFB that contribute to the development of albuminuria.…”
Section: Discussionmentioning
confidence: 99%
“…The present study confirmed the presence and passage of albumin-containing vesicles in the Bowman’s space in the rat PAN model. A recent report documented the rupture of albumin-containing pseudocysts that resulted in the emptying of the high albumin-containing cyst fluid into the Bowman’s space and downstream the nephron [25]. Albumin endocytosis by injured podocytes and the rupture of albumin-containing large pseudocysts are likely alternative mechanisms of albumin leakage through the GFB that contribute to the development of albuminuria.…”
Section: Discussionmentioning
confidence: 99%
“…1A). Because of strong light scattering, deeper live imaging is currently limited as compared to other organs such as the brain, where less scattering species are present [1,18,19]. Improving imaging depth can be achieved with: 1) an increment in laser power, 2) the use of a high numerical aperture of the objective lens with matched refractive indices of the sample and immersion medium, 3) a long free working distance (e.g., Olympus objectives: XLPLanN 25x/1.05W MP, UPlanSApo 30x/1.05 Silicon oil, XLUMPlanFI 20x/0.95 W), 4) longer excitation wavelength as achieved with an optical parametric oscillator [20,21].…”
Section: Resultsmentioning
confidence: 99%
“…Notwithstanding these limitations, some groups have been successful in deriving assays that might mimic some of the mechanistic processes associated with proteinuric disease 38, 39 and that can be used for drug screening purposes 40 . It will be interesting to determine if high throughput imaging system of podocyte function in vivo can be developed, and the scientific progress of this technique has been reviewed elsewhere 41 .…”
Section: Strategies To Identify Clinically Relevant Targetsmentioning
confidence: 99%